(untitled) (Economics and region, 2022)
The article actualizes the problem of management of higher educational institutions and the search for an effective model of such management. The experience of foreign higher education institutions and their existing management models are analyzed. The requirements for the position of rector (head) of higher educational institutions of Ukraine in accordance with the Law of Ukraine "On Higher Education" are highlighted. Based on the Ukrainian educational legislation it is determined that in Ukraine the rector performs a wide range of functions from representative to economic and administrative. The need to form a new Ukrainian management paradigm in the system of higher education was emphasized. It is emphasized that Ukrainian higher education institutions more than ever need smart management, not usurpation of power by persons who have long been rectors. It is concluded that modern management is not a set of the only correct management methods, ready-made recipes and correct answers to all questions. The analysis among Ukrainian higher education institutions with an atypical management model is carried out. It is concluded that successful Ukrainian higher education institutions are looking for an effective management model for the purpose of progressive functioning and development. The positive assessment of the management model "the president is a mentor who takes care of strategic development, the rector is responsible for the current management of the higher education institution" is substantiated. It is proved that the need to develop a new Ukrainian management paradigm is due to modern realities and challenges facing Ukrainian higher education today. It was emphasized that the management of a successful higher education institution is a theory, technology and art of management, which is constantly replenished with a bank of the latest ideas, concepts, observations, practical recommendations, cooperation, access to which makes it possible to consciously comprehend and perform the duties of a leader as a professionally trained and functionally aware leader.